Quality of Life and Social Support among Parents of Adolescence with Thalassemia - Apriani, Desi; Mardhiyah, Ai; Mulya, Adelse Prima; Lukman, Mamat; Maryam, Nenden Nur Asriyani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Thalassemia major causes sufferers to experience severe anemia. This can impact parents’ daily lives as a caregiver of adolescents with thalassemia and makes social support important. Objective: This study aims to identify the relationship between social support and quality of life in parents who have adolescent children with thalassemia major at dr.Slamet Garut Regional Hospital. Method: A cross-sectional approach was applied in this study, which included 64 parents of adolescents with thalassemia major (10-18 years old) who were selected using a consecutive sampling technique. Quality of life values were assessed using the World Health Organization Quality of Life Brief Version (WHOQoL-BREF) and social support was scored using the Multidimensional Scale Of Perceived Social Support (MSPSS). The WHOQoL-BREF is a valid (r=0.390-0.798) and reliable (α=0.941) instrument, as is the MSPSS questionnaire (α=0.920). Spearman correlation test was used for bivariate analysis. Results: There 52 respondents (81.2%) had high social support and 61 respondents (95.3%) with a good quality of life. The results of the correlation analysis revealed a significant relationship that exists between social support and parents' quality of life with a correlation coefficient = 0.447 (p<0.05). Conclusions: Therefore, this research concluded that there is a relationship between social support and quality of life among parents of adolescents with thalassemia major at dr.Slamet Garut Regional Hospital. High social support can improve parents’s quality of life as a caregiver.